Water quality study and water quality status using Storet and index method pollutants in Ratah River Mahakam Ulu Regency, East Kalimantan - Huvat, Antonius Gelung; Kartika, Rudi; Mustakim, Moh.; Ilang, Yerwanto (Edelweiss Applied Science and Technology, 2025)
The Ratah River is the largest subwatershed of the Mahakam River, located in the Mahakam Ulu Regency. The water of the Ratah River is utilized by surrounding communities along its banks for daily activities such as drinking, cooking, and washing. In addition to settlements along the river, there are several permits, including palm oil business permits (IUP), palm oil mills (PKS), forest utilization business licenses (PBPH), and mining permits for coal. This study aims to analyze the water quality and status of the Ratah River in Mahakam Ulu Regency, East Kalimantan, using the Storet method and Pollution Index (IP). Data were obtained from measurements of physical, chemical, and biological parameters at four observation stations representing upstream to downstream areas. The analysis results indicate that most parameters do not meet class I environmental quality standards (Government Regulation No. 22 of 2021). Based on the Storet method, during the dry and rainy seasons, all parameter stations exceeding the quality standard are COD; during the rainy season, all parameter stations exceeding the standard are Fecal Coli; while at stations II and III during the dry season and station I during the rainy season, the parameter exceeding the standard is TSS. The water quality status at most stations falls into the lightly to moderately polluted category. Meanwhile, according to the Pollution Index method, most stations indicate light to moderate pollution.